2020
DOI: 10.1214/20-ecp314
|View full text |Cite
|
Sign up to set email alerts
|

New asymptotics for the mean number of zeros of random trigonometric polynomials with strongly dependent Gaussian coefficients

Abstract: We consider random trigonometric polynomials of the formwhere (a k ) k≥1 and (b k ) k≥1 are two independent stationary Gaussian processes with the same correlation function ρ : k → cos(kα), with α ≥ 0. We show that the asymptotics of the expected number of real zeros differ from the universal one 2 √ 3 , holding in the case of independent or weakly dependent coefficients. More precisely, for all ε > 0, for all ∈ ( √ 2, 2], there exists α ≥ 0 and n ≥ 1 large enough such thatwhere N (fn, [0, 2π]) denotes the num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Hence in the case of a spectral measure admitting a spectral density with respect to the Lebesgue measure, the expected number of real zeros has a whole spectrum of possible values. This has to be compared with the purely discrete case studied in [Thi20], where as recalled above, it is shown that, choosing µρ as purely atomic of the form µρ = 1 2 (δα + δ−α), with α ∈ πQ also yields non-universal nodal asymptotics ranging this time in the interval [ √ 2, 2].…”
Section: Main Results and Commentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence in the case of a spectral measure admitting a spectral density with respect to the Lebesgue measure, the expected number of real zeros has a whole spectrum of possible values. This has to be compared with the purely discrete case studied in [Thi20], where as recalled above, it is shown that, choosing µρ as purely atomic of the form µρ = 1 2 (δα + δ−α), with α ∈ πQ also yields non-universal nodal asymptotics ranging this time in the interval [ √ 2, 2].…”
Section: Main Results and Commentsmentioning
confidence: 99%
“…Recently in [Thi20], the author studied the case where the random coefficients still form a stationary Gaussian process, but the associated spectral measure in purely singular, namely ρ(k) = cos(kα) with α ∈ Q such that µρ = δα+δ −α 2…”
Section: Introductionmentioning
confidence: 99%